The reality of teachers' use of the problem-solving strategy in teaching mathematics according to second-generation curricula for middle school students - Sellama, Hanane Kaouther; Boulkamh, Mohamed (Journal of Human Sciences, 2024)
The objective of this study is to know "the reality of middle cycle teachers’ use of the problem-solving strategy in the teaching of mathematics according to the second generation programs and to identify the main difficulties they encounter in the application of this strategy.The results of this study showed that middle cycle teachers use the problem-solving strategy in the teaching of mathematics according to the second-generation programs with a low rate with an average of (1.13).The two researchers also obtained that teachers encounter difficulties in applying the problem-solving strategy with an average of (1.35), such as the lack of success of the teacher in the choice of the problem. The mathematics program does not meet the needs of the student, because the different situations and activities integrated into it are not suitable for the use of this method.